2020
DOI: 10.1017/s0266462320001919
|View full text |Cite
|
Sign up to set email alerts
|

Toward a common understanding of competencies for health technology assessment: enhancing educational and training programs around the globe

Abstract: Background Depending on the health system context and the demands of relevant stakeholders in countries, the need, organizational structure, and prerequisites for enabling capacity building and development in health technology assessment (HTA) will vary. Core competencies are instrumental in this and include essential knowledge, skills, and attitudes (KSAs). They provide building blocks for delivering high-quality and effective practices of HTA. We aimed to systematically explore and develop an overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…HTA requires multi-disciplinary skills and core competencies, which should be synergistically involved and empowered. A recent article on capacity building in HTA agencies reported the ability to design, conduct, evaluate and to understand HTA applications to decision making, as the main training needs for an efficient and effective HTA process ( 78 ). According to the proposal by the HTAi Scientific Development and Capacity Building Committee, HTA capacity building represents a much broader suite of activities than simply training of core HTA staff in technical competencies ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…HTA requires multi-disciplinary skills and core competencies, which should be synergistically involved and empowered. A recent article on capacity building in HTA agencies reported the ability to design, conduct, evaluate and to understand HTA applications to decision making, as the main training needs for an efficient and effective HTA process ( 78 ). According to the proposal by the HTAi Scientific Development and Capacity Building Committee, HTA capacity building represents a much broader suite of activities than simply training of core HTA staff in technical competencies ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few essential hard/scientific skills (e.g., search and critical appraisal of literature, statistics, economic analysis) and soft skills (e.g., management, writing, interaction with team members, consensus building) were identified by the workshop participants [12]. As a follow-up, Mueller and colleagues conducted four interlinked research activities (including handbook/toolkit reviews, workshops, and surveys via questionnaires) between 2016 and 2019 and identified a list of competencies needed for HTA [13]. Currently, HTA programs in educational institutions around the world are diversified, and the consensus on core competencies is still being established among the stakeholders involved in HTA.…”
Section: Discussionmentioning
confidence: 99%
“…HTA has recently been redefined by an international joint task group as a "multidisciplinary process that uses explicit methods to determine the value of a health technology at different points in its life cycle". 1 It's useful to spend a minute unpacking that definition. What disciplines are involved and who are the primary drivers of the process?…”
Section: Editor's Cornermentioning
confidence: 99%